Implementation of renal key performance indicators: Promoting improved clinical practice. (March 2015) - Toussaint, Nigel D; McMahon, Lawrence P; Dowling, Gregory; Soding, Jenny; Safe, Maria; Knight, Richard; Fair, Kathleen; Linehan, Leanne; Walker, Rowan G; Power, David A
Abstract Aim In the Australian state of Victoria, the Renal Health Clinical Network (RHCN) of the Department of Health Victoria established a Renal Key Performance Indicator (KPI) Working Group in 2011. The group developed four KPIs related to chronic kidney disease and dialysis. A transplant working group of the RHCN developed two additional KPIs. The aim was to develop clinical indicators to measure performance of renal services to drive service improvement. Methods A data collection and benchmarking programme was established, with data provided monthly to the Department using a purpose‐designed website portal. The KPI Working Group is responsible for analysing data each quarter and ensuring indicators remain accurate and relevant. Each indicator has clear definitions and targets, and assess (i) patient education, (ii) timely creation of vascular access for haemodialysis, (iii) proportion of patients dialysing at home, (iv) incidence of dialysis‐related peritonitis, (v) incidence of pre‐emptive renal transplantation, and (vi) timely listing of patients for deceased donor transplantation. Results Most KPIs have demonstrated improved performance over time with limited gains notably in two: the proportion of patients dialysing at home (KPI 3) and timely listing patients for transplantation (KPI 6). Conclusion KPI implementation has been established in Victoria for 2 years, providing performance data without additional funding. The six Victorian KPIs are measurable, relevant and modifiable, and implementation relies on enthusiasm and goodwill of physicians and nurses involved in collecting data. The KPIs require further evaluation, but adoption of a similar programme by other jurisdictions could lead to improved national outcomes.